NEW TENDENCIES IN THE DEVELOPMENT OF ENVIRONMENTAL MOVEMENTS IN THE 21ST CENTURY - Nadić, Darko (Napredak, 2020)
Environmental movements are showing their relevance and innovation trends in the 21st century as well. Environmental problems are still unresolved in this century, the global environmental crisis exists, and the policy of the Green Parties, which arose from environmental movements, has not yielded adequate results. The paper presents the causes of environmental movements as well as their separation from new social movements. In the context of this separation, the paper explore the stages of development of environmental movements from their inception to the present day and compares the activities of these movements, from protest to pacification and marginalization, through "corporate" eco-movements, to the creation of so-called eco communities which can figure as environmental movements in the future. Based on the development of environmental movements so far, their future in this century is being considered, as well as new tendencies and trends. In this sense, the subject of analysis are movements such as the “Economy for the Common Good” which aims not only environmental but also complete social transformation, but also current and ad hoc movements such as "Extinction Rebellion" and "Fridays for Future".